Penanaman Bibit Jagung sebagai Upaya Ketahanan Pangan dalam Program Desa Mandiri Pangan di Desa Takaras, Kecamatan Manuhing, Kabupaten Gunung Mas - Asul Azis Ansyarullah; Dendy; Bagus Suryanatha, Ida (Redtech Putra Benua, 2025)
The Community Service Program (Kuliah Kerja Nyata / KKN) is a form of student engagement aimed at contributing to village development through empowerment activities. This article reports the implementation of the food self-sufficiency program in Takaras Village, Manuhing Sub-district, Gunung Mas Regency, by cultivating corn seeds on village land. The program was carried out collaboratively by students, local government officials, the village security officer (Bhabinkamtibmas), and the community. The method included preparation through land identification and socialization, collective planting activities, technical assistance, and monitoring of crop growth. The results showed positive responses from the community and indicated that the planted corn grew well, reflecting the fertility of local land and the effectiveness of collective efforts. The involvement of Bhabinkamtibmas not only strengthened security but also provided motivation and technical support, ensuring continuity of the program. This activity has proven to increase local food availability, foster community participation, and potentially support economic development through future diversification of corn-based products. Overall, the corn planting program demonstrates that student- community collaboration can be an effective strategy to strengthen the Desa Mandiri Pangan initiative and promote sustainable food security at the village level